2018
DOI: 10.1055/s-0037-1601863
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Cervical Part of the Hypoglossal Nerve

Abstract: Iatrogenic injuries to cranial nerves, half of which affect the hypoglossal nerve, occur in up to 20% of surgical procedures involving the neck. The risk of injury could be minimized by in-depth knowledge of its positional and relational anatomy. Forty-one hypoglossal nerves were dissected from cadaveric specimens and positions described in relation to the internal carotid artery (ICA), external carotid artery (ECA), carotid bifurcation, mandible, hyoid bone, mastoid process, and the digastric tendon. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The hypoglossal nerve is a paired cranial nerve, arising from its nuclei in the medulla, which exits the skull base via the hypoglossal canal and passes deep into the internal jugular vein and superficial to the carotid arteries, mainly crossing superior to the carotid bifurcation. 5 The nerve then passes above the hyoid bone, goes in between the mylohyoid and hyoglossus muscles, and finally supplies all the tongue muscles except the palatoglossus. 6…”
Section: Discussionmentioning
confidence: 99%
“…The hypoglossal nerve is a paired cranial nerve, arising from its nuclei in the medulla, which exits the skull base via the hypoglossal canal and passes deep into the internal jugular vein and superficial to the carotid arteries, mainly crossing superior to the carotid bifurcation. 5 The nerve then passes above the hyoid bone, goes in between the mylohyoid and hyoglossus muscles, and finally supplies all the tongue muscles except the palatoglossus. 6…”
Section: Discussionmentioning
confidence: 99%
“…There were studies evaluating the level of CB according to the mastoid process, gonion, hyoid bone, and thyroid cartilage [ 1 , 4 , 5 , 9 , 16 , 17 , 24 - 27 ]. Some of them evaluated this relationship as a relative position [ 5 , 9 , 17 , 24 ], some by specifying distance [ 25 , 27 ], and some as a combined [ 1 , 4 , 16 , 26 ]. Two of these studies were CTA [ 4 , 16 ], and the others were cadaveric studies.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between our study and that of Klosek et al was that they did not identify a difference between the sexes. The position of the CB relative to the thyroid cartilage was evaluated as "above" by 70% or more in some studies [ 1 , 4 , 16 , 24 , 26 ]. In one study, this rate was at 55%, while it was reported to be at the same level as 39% [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relations between the HN and the ECA can be classified into three types [32,33]. Type I-the HN crossing the ECA inferior to the origin of the OA.…”
Section: Carotid Arteriesmentioning
confidence: 99%